Tunable dextran retention of MXene-TiO2 mesoporous membranes by adjusting the 2D MXene content. (11th July 2018) - Sun, Yuqing; Xu, Zhi; Zhuang, Yongxiang; Liu, Guozhen; Jin, Wanqin; Liu, Gongping; Jing, Wenheng
Abstract: MXene-TiO2 mesoporous membranes on α -Al2 O3 hollow fiber supports are prepared and regulated by adjusting the two-dimensional (2D) MXene content. The prepared MXene-TiO2 membranes are characterized by scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy and x-ray diffraction. The results show that TiO2 nanoparticles (NPs) are uniformed deposited on 2D platforms and that the 2D structure of the original MXenes is still preserved in the film after calcination, thereby successfully inhibiting sol infiltration into the porous support. The obtained MXene-TiO2 layer with a controllable thickness exhibits 'ideal' pathways (longitudinal-lateral transport nanochannel) for dextran molecules between the TiO2 NPs and MXene nanosheets. Furthermore, the MXene-TiO2 membranes show higher rejection performance of dextran with increasing 2D MXene content. The optimal mesoporous MXene-TiO2 hollow fiber membranes exhibit a cut-off molecular weight (MWCO) of 14 854 Da and a high pure water flux of 102 l m −2 h −1 per bar, thereby showing good potential as high-performance interlayers for ceramic nanofiltration membranes.